New materialist approaches to the study of language and identity: Assembling the posthuman subject - de Freitas, Elizabeth; Curinga, Matthew X. (Curriculum inquiry, 2015)
Emphasis on discourse and language-use has fueled the study of identity in education over the last few decades. This paper argues that these approaches fail to fully account for the complex materiality of life, and should be supplemented by new materialist tools for studying language as material. This new materialist approach considers language outside of the usual information-communication model. We argue that this approach is fruitful in studying identity, offering a path around the agency-structure binary where language either serves the subject in self-determination or the institution in furthering normative control. Identity can be studied as an assemblage that does not begin or end in the individual, but partakes of a dynamic affective force field luring posthuman subjects into activity.